ACCOUNTING SKILLS GAP IN THE DIGITAL TRANSFORMATION ERA - Kevin Annabel Wijaya; Ani Wilujeng Suryani; I Gusti Ary Suryawathy (Universitas Airlangga, 2026)
This study aims to analyze the professional skills required of accountants in Indonesia, Malaysia, and Singapore in facing the digital transformation. The method used is content analysis of 1,236 job advertisements on jobstreet.com, classified into five categories of professional skills according to International Education Standards, namely intellectual, interpersonal and communication, personal, organizational, and technical skills. The data were analyzed using the Kruskal-Wallis and Mann-Whitney U tests to determine the differences in skills between countries and job fields. The results showed that there were differences in the skills required, with Indonesia requiring more technical skills due to its focus on efficiency and digitization, while Malaysia and Singapore emphasized personal skills such as responsibility, adaptability, and work ethics. Meanwhile, the accounting field also requires a different focus on skills, where finance requires interpersonal skills, auditing requires personal and organizational skills, while taxation requires more technical and analytical skills. These findings have implications for accounting graduates to be able to prepare the professional skills needed in the world of work in order to be able to compete in the era of industry 5.0.